2009
DOI: 10.17221/1061-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cereal Product Safety by Enzymatic Way of Acrylamide Mitigation

Abstract: Acrylamide as a probably carcinogenic compound is known to be formed in many high thermally treated products with a natural occurrence of amino acid asparagine and reducing sugars as well. Cereal products, especially gingerbreads are extensively affected by acrylamide formation up to 1000 μg/kg and more. This study compares pros and cons of enzyme treatment and a substitution of ammonium raising agent for sodium salt addition in manufactured gingerbreads with respect to their final sensory quality. More than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 1 publication
0
5
1
1
Order By: Relevance
“…The highest AA reduction achieved in the present study was an 86% decrease (compare the A and SCaC variants shown in Fig. ), which is less than the 97% decrease reported by Ciesarová et al using asparaginase. However, in contrast to their experiment, the present study suggests an easy and an inexpensive alternative for the production of gingerbread.…”
Section: Resultscontrasting
confidence: 75%
“…The highest AA reduction achieved in the present study was an 86% decrease (compare the A and SCaC variants shown in Fig. ), which is less than the 97% decrease reported by Ciesarová et al using asparaginase. However, in contrast to their experiment, the present study suggests an easy and an inexpensive alternative for the production of gingerbread.…”
Section: Resultscontrasting
confidence: 75%
“…In the food industry, the Maillard reaction is used for its positive effect in food products such as color modification, texture improvement, and flavor formation, for enhancing the food palatability [37] of baked food [38,39], cocoa and coffee [40]. Despite the positive effects, the Maillard reaction can also cause negative impact in food, ranging from texture, flavor, and color changes to the formation of potentially toxic compounds with negative health effects (ACR, HMF, furans, and heterocyclic amines).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the dose of asparaginase that must be used it was reported that a level of 500 U/Kg was enough for good results regarding the AA reduction level in biscuit products [ 30 ]. In gingerbread the reduction of AA was higher than 97% without any significant changes of the sensory characteristics of the finished product obtained from dough which was left for 48 h at ambient temperature with an enzyme addition level of 1000 U/kg of dough [ 114 ].…”
Section: Methods To Reduce the Acrylamide Content In Bakery Productsmentioning
confidence: 99%